Administrative elites in the Netherlands from 1980 to 2011: making the invisible visible. (December 2014) - Raadschelders, Jos; Meer, Frits M. Van der
The Dutch top civil service level has seldom been described in 'elitist' terms; befitting a country with a strong egalitarian social culture. Though formally open to outside recruitment, in practice the (top) civil service in central government is a rather closed system. There is relatively little occupational mobility between these civil servants and political officeholders, and virtually none between the public and the private sectors. However, some initiatives have recently been taken to improve this external mobility. New Public Management has had little impact upon the structure and functioning of the Dutch administrative elites. More important for the positioning and functioning of these civil servants has been the creation of the Senior Executive Service, and, within the SES, the top management group. By creating this career system at the very top of the civil service at the central level, the elite nature of the top civil servants has been reinforced. Points for practitioners: The structure and functioning of the Dutch civil service has not been influenced by New Public Management (NPM). The rotation of positions at the top, through the Senior Public Service, is mainly inspired by the effort to decrease the compartmentalization of government departments. What has changed is the environment in which higher civil servants work, with Parliament, media and citizens demanding fast and tangible results.